Patterns of Interorganizational Communications and the Diffusion of a Major Technological Innovation in a Competitive Industrial Community - Czepiel, John A. (Academy of Management Journal, 1975)
The effects of interorganizational communications and position in informal communication networks on the decision to adopt a major technological innovation are studied. Based on the sociological diffusion model, a functioning interorganizational communications network was found to be active in the diffusion process.